Efektifitas Kombinasi Terapi Oksigen Hiperbarik dan Gel Teripang Emas (Stichopus hermanii) terhadap Peningkatan Jumlah Osteoblas pada Tikus Diabetes Melitus yang Diinduksi Bakteri Porphyromonas gingivalis - Safina Majdina; Dian Mulawarmanti; Yoifah Rizka (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2016)
Background: The prevalence of diabetes mellitus (DM) is quite high in the world and Indonesia. Diabetes mellitus with poor glycemic control periodontitis as a complication the largest in the oral cavity which causes damage to the alveolar bone. Osteoblasts synthesize osteoid collagen to form bone as raw material. Oxygenation high pressure is able to increase the amount of alveolar bone osteoblasts in patients with DM. Sea cucumber contains growth factors that play a role in the differentiation of osteoblasts to bone formation. Purpose: To determine the effectiveness of combination hyperbaric oxygen therapy 2.4 ATA and sea cucumber gel 3% in the increasing of osteoblasts in rats with DM induced P.gingivalis. Materials and Methods: The study design was factorial design group. Rats are inducted with STZ single dose 65 mg/kg BB to make DM and are inducted with P.gingivalis 1x109 sel/ml to make them suffer periodontitis. Twenty male Wistar rats were divided into five groups. K-(without treatment); K1 (Streptozotocin + P.gingivalis); K2(Streptozotocin + P.gingivalis + sea cucumber gel); K3 (Streptozotocin+ P.gingivalis + HBO); K4 (Streptozotocin +P.gingivalis +HBO + sea cucumber gel). Result: One-way ANOVA here were significant differences (p<0.05) in K2 (24.97 ± 4.99), K3 (22.80 ± 6.45), K4 (28.47 ± 3.20) that compared with K1 (9.22 ± 4.95). Conclusion: Each hyperbaric oxygen therapy doses of 2.4 ATA 100% O2 3x30 minutes with 5 minute intervals for 7 days and sea cucumber gel (Stichopus hermanii) concentration of 3% and a combination of both therapies showed an increase of osteoblasts significantly in rats with diabetes mellitus induced P.gingivalis.